Geopolymer regenerated fireproof mortar based on porous light filler and preparation method of geopolymer regenerated fireproof mortar

By using porous light fillers and alkali exciters and regenerated fireproof mortars, the problems of high cost of building fireproof coating and degradation of silicate mortar at high temperatures are solved, and high temperature stability is achieved and recycling, extend the time of fire deterioration, improve the compressive strength after the fire, and provide guarantees for safety in fire scenarios.

CN119306435APending Publication Date: 2025-01-14CHANGZHOU UNIV

Patent Information

Application Number
CN202411458233.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing fire-proof coatings are costly and are prone to emitting irritating gases in high temperature environments. The silicate mortar is easily affected by high temperature bursts, resulting in loss of structural bearing capacity. The performance of the metakaolin base polymer mortar deteriorates sharply at high temperatures and absorbs water. High sex leads to early strength loss.

Method used

Porous light fillers, such as fly ash hollow microbeads, are prepared with alkali triggers and regenerated fine aggregates to prepare the regenerated fire-proof mortar. Through dry mixing, stirring and curing, it forms a viscous fluid, simulates high-temperature tests to improve Refractory performance.

Benefits of technology

Significantly extend the time of high temperature deterioration, improve residual compressive strength, reduce CO2 emissions, reduce the use of natural resources, provide green gelling materials, have acid and alkali corrosion resistance, high strength and other characteristics, reduce fire hazards, have good high temperature resistance and social economy benefit.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses geopolymer regenerated fireproof mortar based on porous light filler and a preparation method of the geopolymer regenerated fireproof mortar. The fireproof mortar is prepared from the following raw materials: 460 to 520 parts of cementing material, 210 to 360 parts of porous light filler, 330 to 380 parts of alkali activator, 120 to 500 parts of regenerated fine aggregate and 180 to 280 parts of water, the porous light filler is preferably selected from fly ash hollow microspheres. The preparation method comprises the following steps: uniformly mixing the cementing material, the porous light filler and the recycled fine aggregate to obtain a dry mixture; and adding an alkali activator into the dry mixture to obtain the geopolymer regenerated fireproof mortar. And after the age is reached, demolding and curing are carried out. By utilizing the characteristics of high porosity, low heat conductivity coefficient and the like of the porous light filler, the heat preservation and heat insulation capabilities of the geopolymer regenerated mortar are improved, the fireproof performance of the geopolymer mortar is greatly improved, and meanwhile, the resource utilization of solid wastes is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a geopolymer regenerated fireproof mortar based on porous lightweight filler and a preparation method thereof. Background Art

[0002] With the continuous advancement of urbanization, the harm of construction waste to the environment has intensified. Recycled fine aggregate is a solid particle with a particle size of less than 4.75 mm obtained in the crushing process of construction solid waste. It has high water absorption rate, low crushing index, and cannot be directly recycled. Recycled fine aggregate piled in the open air is easy to pollute air and water resources. The resource utilization of recycled fine aggregate and its development into a recycled fireproof mortar can effectively solve the problem of recycling construction waste.

[0003] Building fire is one of the important factors threatening the safety of human life and property. As the main method of building fire protection, coating has high cost for large-scale use and is easy to emit irritating gases in high temperature environment. Porous lightweight fillers have the characteristics of large specific surface area, rich pores, low thermal conductivity, and low density. They can promote the volcanic ash effect under high temperature and generate zeolite-like structures to provide strength support for hydration products. Replacing it with geopolymer recycled mortar prepared from recycled fine aggregate and alkali activator after crushing construction waste has great value in enhancing the fire resistance of recycled fireproof mortar.

[0004] Ordinary silicate mortar is susceptible to high-temperature bursting, causing the structure to lose its bearing capacity. Geopolymer is an amorphous three-dimensional structure generated by alkaline activators (NaOH and Na2SiO3 or KOH and Na2SiO3) and precursor materials (metakaolin, fly ash, red mud, etc.). This inorganic three-dimensional structure itself cannot burn and has high-temperature stability. It has broad application prospects in the field of building fire protection. Its preparation process is low-carbon and clean, reducing CO2 emissions by about 80%~90%, reducing the frequency of use of natural resources such as sand and stone, and increasing the utilization rate of industrial waste or industrial by-products. At the same time, it has the characteristics of acid and alkali corrosion resistance and high strength, which greatly improves its potential value as a green cementitious material. However, the performance of metakaolin-based polymer mortar deteriorates sharply when the temperature is greater than 600℃. In the early stage of hydration, metakaolin has high water absorption, resulting in incomplete geopolymerization reaction, so the early strength loss is large. Geopolymer mortar will produce a certain amount of self-shrinkage during the curing process, and undergo a shrinkage-expansion process under high temperature conditions, inducing microcracks to develop. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a geopolymer regeneration fireproof mortar based on porous lightweight fillers and a preparation method thereof, which realizes the resource utilization of solid waste, prolongs the high temperature deterioration time, improves the residual compressive strength after high temperature action, maintains high temperature integrity, and can significantly reduce the harm caused by fire.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: The first aspect of the present invention provides a geopolymer regenerated fireproof mortar based on porous lightweight filler, comprising the following components in parts by weight: 460-520 parts of cementitious material, 210-360 parts of porous lightweight filler, 330-380 parts of alkali activator, 120-500 parts of recycled fine aggregate, and 180-280 parts of water.

[0007] Preferably, the geopolymer regenerated fireproof mortar based on porous lightweight filler comprises, by weight: 460-520 parts of cementitious material, 210-290 parts of porous lightweight filler, 330-380 parts of alkali activator, 240-500 parts of recycled fine aggregate, and 180-280 parts of water.

[0008] Further preferably, the geopolymer recycled fireproof mortar based on porous lightweight filler comprises, by weight: 490 parts of cementitious material, 210-290 parts of porous lightweight filler, 353 parts of alkali activator, 240-500 parts of recycled fine aggregate, and 210 parts of water.

[0009] Preferably, the cementitious material is kaolin with a moisture content of less than 30%, a SiO2 content of greater than 40%, and an Al2O3 content of greater than 30%.

[0010] Preferably, the porous lightweight filler is fly ash hollow microspheres with a particle size of 0.074-0.15 mm, a water absorption rate of less than 20%, a SiO2 content of more than 50%, and an Al2O3 content of more than 30%. Fly ash hollow microspheres are an ultrafine powder material screened from fly ash from power plants, and have the characteristics of light weight, high compressive strength, and good thermal stability.

[0011] Preferably, the volume of the porous lightweight filler accounts for 60% to 100% of the total volume of the porous lightweight filler and the recycled fine aggregate.

[0012] Preferably, the alkaline activator is a mixed solution of NaOH and Na2SiO3, the NaOH solid purity is greater than 92%, the Na2SiO3 solution modulus is 1.2, the Na2O·nSiO2 content is 42%, and the Baume degree is 50.

[0013] Preferably, the recycled fine aggregate is solid particles of construction waste crushed and ground to a particle size of less than 4.75 mm, with an apparent density of 2000-2600 kg / m3 , water absorption is less than 10%, and mud content is less than 3%.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned geopolymer regenerated fireproof mortar based on porous lightweight filler, comprising the following steps: The cementitious material, porous lightweight filler and recycled fine aggregate are dry-mixed and uniformly mixed to obtain a dry mixture; an alkali activator and water are added to the dry mixture, and the mixture is stirred to obtain a viscous fluid, namely, the geopolymer recycled fireproof mortar; the mixture is molded and compacted in layers, and after reaching the age, the mixture is demolded and cured.

[0015] Preferably, the cementitious material, porous lightweight filler and recycled fine aggregate are dry mixed for 60 s to 120 s; an alkali activator is added to the dry mix and stirred for 120 s to 180 s; Preferably, the curing conditions are natural curing for 1 d to 2 d, high temperature curing at 60°C to 100°C for 1 d to 2 d, and standard curing (temperature of 20±2°C, relative humidity ≥95%) for 5 d to 10 d.

[0016] Preferably, the test block size of the geopolymer high temperature fireproof mortar before and after high temperature is 50 mm*50 mm*50 mm.

[0017] Preferably, a GS-60-1200F fire-resistant high temperature testing machine is used to simulate the high temperature test. The simulated high temperature test temperature is 800°C, the heating rate is 700°C / h, and the temperature is kept constant for 2 hours after heating to the target temperature. After the high temperature test is completed, it is naturally cooled to room temperature.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The porous lightweight filler mainly composed of fly ash hollow microspheres has a low thermal conductivity coefficient, which can greatly reduce the density of geopolymer mortar. It is hollow inside and filled with inert gas, which hinders the conduction of heat and can achieve the effect of heat preservation and heat insulation. At the same time, the fly ash hollow microspheres have volcanic ash activity, which improves the initial strength of the geopolymer mortar during the high-temperature curing process, and can still maintain volume stability under high temperature. As a high-temperature resistant material, it has potential advantages in high-temperature environments. The present invention utilizes the lightweight and high-strength characteristics of fly ash hollow microspheres to reduce the thermal conductivity of geopolymer mortar and hinder heat conduction. At the same time, the high volcanic ash activity of the fly ash hollow microspheres improves the early strength of the geopolymer slurry and reduces the strength degradation caused by thermal expansion deformation.

[0019] The present invention adopts porous lightweight fillers to prepare geopolymer regeneration fireproof mortar, which has good high temperature resistance, simple preparation process, reduced production cost, and significant social and economic benefits. Compared with silicate mortar, geopolymer mortar reduces carbon emissions during preparation and transportation, and alleviates CO2 pollution to the environment; using recycled fine aggregate and porous lightweight fillers, waste can be recycled to obtain lightweight, high-strength, fire-resistant geopolymer regeneration mortar; the geopolymer regeneration fireproof mortar prepared by the present invention prolongs the fire degradation time, improves the residual compressive strength after the fire, and provides protection for the safety of human life and property in fire scenes. DETAILED DESCRIPTION

[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0022] The present invention provides a geopolymer regenerated fireproof mortar based on porous lightweight filler, and the mass of each component is determined according to the following proportions: The volume of aggregate (recycled fine aggregate + porous lightweight filler) accounts for 51.6% of the total volume of mortar, the volume of porous lightweight filler accounts for 60%~80% of the total volume of aggregate, the volume of cementitious material accounts for 19.2% of the total volume, the volume of alkali activator (NaOH+Na2SiO3+H2O) accounts for 23.96% of the total volume, and water accounts for 5.3% of the total volume.

[0023] The porous lightweight filler used in the following specific embodiments of the present invention is fly ash hollow microspheres, produced by Henan Borun Casting Materials Co., Ltd., with a water absorption rate of 15% and a bulk density of 300 kg / m 3 , particle size is 0.074~0.15 mm, SiO2 content is 60.12%, and Al2O3 content is 33.27%.

[0024] The chemical composition of metakaolin is 44.17% SiO2, 38.22% Al2O3, 8.16% Fe2O3, 4.91% CaO, 1.72% TiO2, with a moisture content of 29%, an activity index of 103% at 7 days, and an activity index of 112% at 28 days; The chemical composition of the porous lightweight filler is 60.12% SiO2, 33.27% Al2O3, 2.34% Fe2O3, 1.12% MgO, the water absorption rate is 20%, and the bulk density is 400 kg / m 3 ; The concentration of NaOH solution is 12 mol / L; the modulus of Na2SiO3 is 1.2, the content of Na2O·nSiO2 is 42%, and the Baume degree is 50; The apparent density of recycled fine aggregate is 2396 kg / m 3 , the water absorption rate is 8.8%. Example 1

[0025] This embodiment provides a method for preparing geopolymer regenerated fireproof mortar, comprising the following steps: (1) Weigh the raw materials according to the following formula: 490 parts of cementitious material (metakaolin), 210.5 parts of porous lightweight filler (hollow fly ash microspheres), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), 495.4 parts of recycled fine aggregate, and 210 parts of water.

[0026] (2) Preparation of geopolymer recycled fireproof mortar Prepare the alkali activator 24 h in advance, pour the measured distilled water into a beaker, then add the NaOH solid particles, stir with a glass rod to dissolve, and finally pour in the Na2SiO3 solution, stirring in a clockwise direction with a glass cup for 15 s. Dry mix the recycled fine aggregate, cementitious material and porous lightweight material for 60 s to obtain a dry mix. Slowly add the alkali activator to the dry mix in turn, stirring for 60 s while adding, and stir for another 60 s after the alkali activator is completely poured into the dry mix.

[0027] (3) Moulding and maintenance Spray the release agent into the mold, put the geopolymer regeneration fireproof mortar into the mold and tamp it layer by layer, place it on a vibration table for 10 seconds, and wrap it with polyethylene film after the surface solidifies. Place the geopolymer regeneration fireproof mortar and the mold in a natural environment at 25℃ for 1 day. After demoulding, put the test block into a sealed bag and place it in an oven at 85℃ for high temperature curing for 1 day. After high temperature curing, take out the test block, cool it down, and place it in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for curing until 7 days old, and test the corresponding physical and mechanical properties.

[0028] (4) High temperature test The geopolymer recycled fireproof mortar was placed in a high temperature test chamber. The simulated high temperature test temperature was 800℃, the heating rate was 700℃ / h, and the temperature was kept constant for 2 h after reaching the target temperature. After the high temperature test, it was naturally cooled to room temperature and the corresponding physical and mechanical properties were tested. Example 2

[0029] This embodiment provides a method for preparing geopolymer regenerated fireproof mortar, and the raw material formula is as follows: 490 parts of cementitious material (metakaolin), 245.6 parts of porous lightweight filler (hollow fly ash microspheres), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), 371.5 parts of recycled fine aggregate, and 210 parts of water.

[0030] The raw materials were weighed according to the formula, and the remaining steps were the same as in Example 1. Example 3

[0031] This embodiment provides a method for preparing geopolymer regenerated fireproof mortar, and the raw material formula is as follows: 490 parts of cementitious material (metakaolin), 280.7 parts of porous lightweight filler (hollow fly ash microspheres), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), 247.7 parts of recycled fine aggregate, and 210 parts of water.

[0032] The raw materials were weighed according to the formula, and the remaining steps were the same as in Example 1. Comparative Example 1

[0033] Comparative Example 1 provides a method for preparing geopolymer recycled fireproof mortar, which is different from Example 1 in that the raw material formula in step (1) is adjusted and recycled fine aggregate is not added. The specific raw material formula is as follows: 490 parts of cementitious material (metakaolin), 350.9 parts of porous lightweight filler (hollow fly ash microspheres), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), and 210 parts of water. Comparative Example 2

[0034] Comparative Example 2 provides a method for preparing geopolymer regenerated fireproof mortar, which is different from Example 1 in that the raw material formula in step (1) is adjusted and no porous lightweight filler is added. The specific raw material formula is as follows: 490 parts of cementitious material (metakaolin), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), 1173 parts of recycled fine aggregate, and 210 parts of water. Comparative Example 3

[0035] This comparative example 3 provides a method for preparing geopolymer regenerated fireproof mortar, which is different from that of Example 1 in that the curing conditions in step (3) are adjusted. Specifically, the following steps are included: (1) Weigh the raw materials according to the following formula: same as Example 1; (2) Preparation of geopolymer regenerated fireproof mortar: same as in Example 1; (3) Moulding and maintenance: Spray the release agent into the mold, load the geopolymer regeneration fireproof mortar into the mold and tamp it layer by layer, place it on a vibration table for 10 seconds, and wrap it with polyethylene film after the surface solidifies. Place the geopolymer regeneration fireproof mortar and the mold in a natural environment at 25℃ for 1 day, and then place it in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for curing until the 7-day age, and test the corresponding physical and mechanical properties.

[0036] (4) High temperature test: same as in Example 1. Comparative Example 4

[0037] Comparative Example 4 provides a method for preparing geopolymer regenerated fireproof mortar, which is different from Example 1 in that the formula raw materials in step (1) are adjusted, and the fly ash hollow microspheres are replaced with vitrified microspheres. The specific raw material formula is as follows: 490 parts of cementitious material (metakaolin), 210.5 parts of porous lightweight filler (vitrified microspheres), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), 495.4 parts of recycled fine aggregate, and 210 parts of water. Comparative Example 5

[0038] Comparative Example 5 provides a method for preparing geopolymer regenerated fireproof mortar, which is different from Example 1 in that the formula raw materials in step (1) are adjusted, and fly ash hollow microspheres are replaced with fly ash. The specific raw material formula is as follows: 490 parts of cementitious material (metakaolin), 210.5 parts of porous lightweight filler (fly ash), 353 parts of alkali activator (40 parts of NaOH solution, 238 parts of Na2SiO3 solution, 75 parts of distilled water), 495.4 parts of recycled fine aggregate, and 210 parts of water.

[0039] The performance of the geopolymer regenerated fireproof mortar test blocks prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested, and the physical and mechanical properties of the geopolymer regenerated fireproof mortar were measured according to GB / T17671-2021 "Test Method for Strength of Cement Mortar" and JGJ / T70-2009 "Standard for Test Method for Basic Performance of Building Mortar", and the results are shown in Table 1. The mass loss rate is expressed as the percentage of the difference in mass before and after high temperature of the test block to the initial mass, and the strength loss rate is expressed as the percentage of the difference in strength before and after high temperature of the test block to the initial strength.

[0040] Table 1 Performance test results of geopolymer recycled fireproof mortar test blocks .

[0041] The results in Table 1 show that the mass loss rate of the geopolymer regeneration fireproof mortar prepared according to Examples 1 to 3 after simulated fire is less than 10%, the strength loss rate is less than 70%, and the residual bonding strength is greater than 1.4 MPa, which can eliminate high-temperature spalling behavior and delay the failure time of the structure, meeting the requirements of engineering use. Fly ash hollow microspheres are industrial byproducts generated by coal combustion in thermal power plants. The hollow inside is filled with negative pressure gas, which has good heat insulation and flame retardant effects, reduces the melting point of the geopolymer slurry, and keeps it thermally stable in an environment of 800°C. At the same time, the high-temperature melting matrix can reversely repair the unfilled holes, thereby reducing the damage caused by high temperature. As the proportion of fly ash hollow microspheres in the total volume of aggregate increases, the recycled fine aggregate cannot provide strength support, and the residual mechanical strength of the geopolymer regeneration mortar after high temperature exposure decreases. Fly ash hollow microspheres have strong adsorption to geopolymer slurry, fill the microcracks of the slurry, and avoid a large loss of strength after high temperature. It is a lightweight heat-insulating fireproof material.

[0042] Compared with Example 1, the mass loss rate of Comparative Example 1 increased by 5.21%, the strength loss rate increased by 14.5%, and the residual bonding strength decreased by 0.3 MPa. In Comparative Example 1, the volume of the porous lightweight filler accounts for 100% of the total volume of the aggregate. There are a large number of extremely fine pores inside the porous lightweight filler, which absorbs a large amount of water in the early stage of hydration. Part of the water is used for the polycondensation reaction of the geopolymer, and the other part is temporarily stored in the micropores of the porous lightweight filler in the form of crystal water. When exposed to a high temperature environment, the geopolymer regeneration mortar mixed with excessive porous lightweight fillers loses too much water, which is the main factor causing its mass loss. Excessive porous lightweight fillers also produce agglomeration and cannot be evenly dispersed in the geopolymer slurry, resulting in excessively high local thermal conductivity, and heat is hindered in the process of transferring to the outside world. The uneven thermal stress induces the generation of cracks inside. When the porous lightweight filler is used as an aggregate instead of the recycled fine aggregate, the aggregate grading is uneven, and no air partition can be generated between the filler particles to delay the heat transfer rate, showing more serious high temperature damage.

[0043] Compared with Example 1, the mass loss rate and residual bonding strength of Comparative Example 2 are reduced, while the strength loss rate is increased. Comparative Example 2 does not incorporate porous lightweight fillers, and the volume of porous lightweight fillers in Example 1 accounts for 60% of the total volume of aggregate. Compared with recycled fine aggregate, porous lightweight fillers have a larger water absorption rate, so the recycled fireproof mortar prepared in Example 1 contains a large amount of pore water. Under high temperature environment, crystal water and pore water are converted from liquid to gaseous state, overflow from the internal passage of the test block, and escape to the external environment, resulting in an increase in mass loss rate. 60% volume of porous lightweight fillers and 40% volume of recycled fine aggregate can obtain a good particle grading, make the solid particles more closely combined, hinder the escape path of pore water, and reduce the strength loss caused by pore water escape. At the same time, the Si element of fly ash hollow microspheres participates in the geopolymerization reaction to generate Si-Al inorganic three-dimensional structure, which improves the stability of geopolymer recycled mortar at high temperature. Its internal hollow structure can reduce the expansion and contraction rate of geopolymer recycled mortar and reduce the risk of cracking.

[0044] Compared with Example 1, in Comparative Example 3, the curing conditions were changed, and standard curing was used instead of high-temperature curing. The results showed that the strength loss rate increased significantly, reaching 70.5%, and the bonding strength deteriorated to 1 MPa. High-temperature curing accelerates the alkali activation process, so that the fly ash hollow microspheres that have not fully reacted during the stirring process undergo a secondary hydration reaction, giving full play to the volcanic ash activity of the fly ash hollow microspheres. Geopolymers can generate zeolite-like structures under high temperature environments, have a high melting point, prolong the high-temperature deterioration time of geopolymer regeneration mortar, and compensate for the adverse effects of high-temperature crack expansion. High-temperature curing obtains a dense gelling system, which wraps the fly ash hollow microspheres and delays the development of cracks under high temperature.

[0045] Compared with Example 1, Comparative Examples 4 and 5 replace hollow fly ash microspheres with vitrified microspheres and fly ash, and the compressive strength and bonding strength are weakened to varying degrees. During the high-temperature curing process, the vitrified microspheres cannot exert the same volcanic ash activity as hollow fly ash microspheres, and fail to react to generate sufficient CASH gel in the later stage of the geopolymerization reaction. At the same time, its surface presents irregular prisms and cannot be fully embedded in the geopolymer matrix during the stirring process. Different from hollow fly ash microspheres, the internal structure of fly ash is dense, and the heat cannot be released in time during the conduction inside the geopolymer mortar, resulting in the accumulation of thermal stress, and the volume expansion of the geopolymer mortar induces cracks.

[0046] The present invention adopts porous lightweight fillers to prepare geopolymer regeneration fireproof mortar, which has good high temperature resistance, simple preparation process, reduced production cost, and significant social and economic benefits. Compared with silicate mortar, geopolymer mortar reduces carbon emissions during preparation and transportation, and alleviates CO2 pollution to the environment; using recycled fine aggregate and porous lightweight fillers, waste can be recycled to obtain lightweight, high-strength, fire-resistant geopolymer regeneration mortar; the geopolymer regeneration fireproof mortar prepared by the present invention prolongs the fire degradation time, improves the residual compressive strength after the fire, and provides protection for the safety of human life and property in fire scenes.

[0047] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A geopolymer regenerated fireproof mortar based on porous lightweight filler, characterized in that: The fireproof mortar comprises, by weight: 460-520 parts of cementitious material, 210-360 parts of porous lightweight filler, 330-380 parts of alkali activator, 120-500 parts of recycled fine aggregate, and 180-280 parts of water; the volume of the porous lightweight filler accounts for 60%-100% of the total volume of the porous lightweight filler and the recycled fine aggregate; the porous lightweight filler is fly ash hollow microspheres.

2. The geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 1, characterized in that: The fireproof mortar comprises, by weight: 460-520 parts of cementitious material, 210-290 parts of porous lightweight filler, 330-380 parts of alkali activator, 240-500 parts of recycled fine aggregate, and 180-280 parts of water.

3. The geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 1, characterized in that: The fireproof mortar comprises, by weight: 490 parts of cementitious material, 210-290 parts of porous lightweight filler, 353 parts of alkali activator, 240-500 parts of recycled fine aggregate, and 210 parts of water.

4. The geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 1, characterized in that: The cementitious material is metakaolin, the moisture content of the metakaolin is less than 30%, the SiO2 content is greater than 40%, and the Al2O3 content is greater than 30%.

5. The geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 1, characterized in that: The particle size of the fly ash hollow microspheres is 0.074-0.15 mm, the water absorption rate is less than 20%, the SiO2 content is greater than 50%, and the Al2O3 content is greater than 30%.

6. The geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 1, characterized in that: The alkaline activator is a mixed solution of NaOH and Na2SiO3, the modulus of the Na2SiO3 solution is 1.2, the content of Na2O·nSiO2 is 42%, and the Baume degree is 50.

7. The geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 1, characterized in that: The recycled fine aggregate is solid particles that are crushed and ground into a particle size of less than 4.75 mm, with an apparent density of 2000-2600 kg / m 3 , water absorption is less than 10%, and mud content is less than 3%.

8. The method for preparing geopolymer regenerated fireproof mortar based on porous lightweight filler according to any one of claims 1 to 7, characterized in that: The following steps are involved: The cementitious material, porous lightweight filler and recycled fine aggregate are stirred evenly to obtain a dry mix; an alkali activator and water are added to the dry mix, and stirred until it becomes a uniform viscous fluid, which is the geopolymer recycled fireproof mortar; the mortar is molded and compacted in layers, and demolded and cured after reaching the age.

9. The method for preparing geopolymer regenerated fireproof mortar based on porous lightweight filler according to claim 8, characterized in that: The curing conditions are natural curing for 1 d~2 d, high temperature curing at 60℃~100℃ for 1 d~2 d, and standard curing (temperature is 20±2℃, relative humidity ≥95%) for 5 d~10 d.

Citation Information

Patent Citations

  • Geopolymer fireproof mortar based on waste porous material and preparation method thereof

    CN117342829A

  • Light nano modified microbead reinforced geopolymer foam concrete and preparation method thereof

    CN117602892A

Cited By

  • Modified geopolymer mortar and application thereof in structural member

    CN120903874A

  • Preparation method of fly ash solidified body suitable for high-temperature incineration environment

    CN122057766A

  • Geopolymer fireproof thermal insulation mortar and preparation method thereof

    CN122403858A

  • Geopolymer recycled fire‑resistant mortar based on porous lightweight filler and preparation method therefor

    WO2026081665A1